MODELING OF RAINFALL IN INDONESIA IN ITS APPLICATION IN AGRICULTURE (Case Study Rice and Corn Plans) - HERMAWAN (NIM : 10108058); Pembimbing : Dr. Nuning Nuraini, CUCU
Agriculture is a very important commodity in Indonesia. In this research, we concern only for an important food crop for people in Indonesia, that are rice and corn. The production of both crops is heavily dependent on the time and place of planting. In order to obtain the ideal conditions for growing rice and corn, modeling was performed taking into account the factor of rainfall. By using daily rainfall data obtained from the TRMM satellite (Tropical Rainfall Measuring Mission), was made to decade, monthly, and yearly rainfall data. Ideal time for planting is done by searching the first decade causing the onset of the rainy season, dry season, rice planting season, and corn planting season. Then, with annual data, we look for the relations between rainfall and crop production of rice and maize using correlation analysis, sample determination analysis, and the t-test. The results from data processing show that the rice crop production areas have linear correlation with rainfall in the province of West Java, Central Java, Banten, West Kalimantan, Central Kalimantan, Gorontalo, West Sulawesi, Maluku, West Papua, and Papua. The corn crop production have linear correlation with rainfall in the province of West Java, Central Java, Yogyakarta, North Sulawesi, Gorontalo, and West Papua.